COVID-19 Food Trade Policy Tracker - CGIAR Research Program on Policies, Institutions, and Markets (2020)
The tracker can be accessed through Tableau Public. It is licensed under a Creative Commons Attribution 4.0 International License. Data is publicly available in csv format.